ANALISIS SISTEM PEMBUMIAN TOWER SALURAN TRANSMISI DARI GARDU INDUK KAPAL – GARDU INDUK GIANYAR - IGP Agung Satya Wicaksana; IW Arta Wijaya; IGN Janardana (Jurnal SPEKTRUM, 2021)
This study aims to improve the earthing value of transmission lines which have an earthvalue less than the standard value off SPLN No 121: 1996, namely 10 and recommend anearthing system that meets the standards. Theemethodduseddissa descriptive method bycalculating the value of the earthing system by following the SPLN standard No. 121: 1996. Thisanalysis consists of several stages, namely a site survey, measuring soil resistance (R) tocalculate the value of soil resistivity (?) then calculating the value of grounding resistance with 5types of grounding systems to achieve grounding resistance 10 , namely one electrodegrounding system, 2 electrode grounding system planted vertically S > L, 2 electrode earthingsystem planted vertically S < L, plate earthing system, and a grid-rod earthing system. Theresults of the research are for paddy fields using a vertical one-electrode earthing system, thevalue is 7.32 ? with a manufacturing cost of Rp. 857,000, on farmland with a vertical oneelectrodeearthing system, the value is 8.36 ? with a manufacturing cost of Rp. 1,363,000, andon clay soil with a vertical one-electrode earthing system, the result is 7.98 ? with amanufacturing cost of Rp. 857,000.